Effect of Emergency Department Mattress Compressibility on Chest Compression Depth Using a Standardized Cardiopulmonary Resuscitation Board, a Slider Transfer Board, and a Flat Spine Board: A Simulation-Based Study. Issue 6 (December 2017) - Cheng, Adam; Belanger, Claudia; Wan, Brandi; Davidson, Jennifer; Lin, Yiqun
Abstract : Introduction: Cardiopulmonary resuscitation (CPR) performed on a mattress decreases effective chest compression depth. Using a CPR board partially attenuates mattress compressibility. We aimed to determine the effect of a CPR board, a slider transfer board, a CPR board with a slider transfer board, and a flat spine board on chest compression depth with a mannequin placed on an emergency department mattress. Methods: The study used a cross-over study design. The CPR-certified healthcare providers performed 2 minutes of compressions on a mannequin in five conditions, an emergency department mattress with: ( a ) no hard surface, ( b ) a CPR board, ( c ) a slider transfer board, ( d ) a CPR board and slider transfer board, and ( e ) a flat spine board. Compression depths were measured from two sources for each condition: ( a ) an internal device measuring sternum-to-spine compression and ( b ) an external device measuring sternum-to-spine compression plus mattress compression. The difference of the two measures (ie, depleted compression depth) was summarized and compared between conditions. Results: A total of 10, 203 individual compressions from 10 participants were analyzed. The mean depleted compression depths (percentage depletion) secondary to mattress effect were the following: 23.6 mm (29.7%) on a mattress only, 13.7 mm (19.5%) on a CPR board, 16.9 mm (23.1%) on a slider transfer board, 11.9 mm (17.3%) on a slider transfer board plus backboard, and 10.3 mm (15.4%) on a flat spine board. The differences in percentage depletion across conditions were statistically significant. Conclusion: Cardiopulmonary resuscitation providers should use a CPR board and slider transfer board or a flat spine board alone because these conditions are associated with the smallest amount of mattress compressibility.